-11x+2=-15x+6

Simple and best practice solution for -11x+2=-15x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11x+2=-15x+6 equation:


Simplifying
-11x + 2 = -15x + 6

Reorder the terms:
2 + -11x = -15x + 6

Reorder the terms:
2 + -11x = 6 + -15x

Solving
2 + -11x = 6 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
2 + -11x + 15x = 6 + -15x + 15x

Combine like terms: -11x + 15x = 4x
2 + 4x = 6 + -15x + 15x

Combine like terms: -15x + 15x = 0
2 + 4x = 6 + 0
2 + 4x = 6

Add '-2' to each side of the equation.
2 + -2 + 4x = 6 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = 6 + -2
4x = 6 + -2

Combine like terms: 6 + -2 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| 6x=112 | | 6r+2=6 | | 54.8-.2d=60.1 | | 15c^2-3c= | | 54.8-.2=60.1 | | 2x-7y-10=o | | x^6y^6-x^5y^4+x^4y^3+x^3y^3=0 | | 0=-16t^2+14+2 | | 20x-110=-490 | | (-4)+-3(5)=-11 | | 7y+3=4 | | .008(3-k)+.09(k-2)=1 | | 3m-6=-33 | | 8x-4(5+2x)=12 | | m-9m-2m-6= | | 4x^3(7)= | | 7x-4+3x-6=90 | | 5x^2+3xy-2y^2= | | 2x+10=6x+12 | | 26x-28x=6-8 | | 6x+21y-26x+64y=0 | | (-2x^6y)(x^7y^5)= | | 9.3z-8.3z-7.2=-5.3+8.4 | | y=11(0.75) | | 10p^2-21p+8=0 | | 8w^2-28w-60=0 | | x^4-2x^2=7x-5 | | (a^2)(b)+3b=cforb | | (a^2)(b)+3b=cforb | | -33+21=-2x+5x | | 2x+4+50=90 | | 100-5x=50 |

Equations solver categories